2020
DOI: 10.1007/s10021-019-00474-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent Growth and Expansion of Birch Shrubs Across a Low Arctic Landscape in Continental Canada: Are These Responses More a Consequence of the Severely Declining Caribou Herd than of Climate Warming?

Abstract: The recent widespread expansion of deciduous shrubs across much of the Arctic has been largely attributed to climate warming. This study investigated decadal growth rates of dwarf birch (Betula glandulosa) across a low Arctic landscape in the continental interior of Canada. Detailed birch cover (100 m 2 replicate plots) and individual shrub stature measurement datasets for five representative habitat-types were compared between 2006 and 2016, and evaluated in relation to environmental characteristics. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…However, the Bathurst herd has experienced dramatic declines over the past several decades, from an estimated 470,000 in 1986 to 32,000 in 2009 and most recently to 8,200 in 2018 (Adamczewski et al 2019). Birch shrub expansion within some landscape patches and birch encroachment across caribou trail pathways illustrated by repeat photography indicate evidence of this caribou herd decline at Daring Lake (Andruko, Danby, and Grogan 2020). Personal observations at our study site also confirmed that only small groups of caribou were regularly observed from 2004 to 2009 (Zamin 2013), and just a few caribou passed through our research valley each summer from 2015 to 2017 (Q. Gu, personal observation).…”
Section: Caribou Exclosure Had No Biomass Impacts On Vascular Plants supporting
confidence: 62%
“…However, the Bathurst herd has experienced dramatic declines over the past several decades, from an estimated 470,000 in 1986 to 32,000 in 2009 and most recently to 8,200 in 2018 (Adamczewski et al 2019). Birch shrub expansion within some landscape patches and birch encroachment across caribou trail pathways illustrated by repeat photography indicate evidence of this caribou herd decline at Daring Lake (Andruko, Danby, and Grogan 2020). Personal observations at our study site also confirmed that only small groups of caribou were regularly observed from 2004 to 2009 (Zamin 2013), and just a few caribou passed through our research valley each summer from 2015 to 2017 (Q. Gu, personal observation).…”
Section: Caribou Exclosure Had No Biomass Impacts On Vascular Plants supporting
confidence: 62%
“…However, the loss of herbivory from the landscape undoubtedly also affected vegetation productivity, and it is challenging to infer causal mechanisms of either landscape change or population change from these trends alone (Andruko et al 2020). Determining the nature and magnitude of the relationship between these two phenomena will require spatial-temporal examination of caribou movement and habitat occupation in relation to the observed changes in productivity and phenology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the increases in maximum and time integrated EVI we observed could be occurring partly in response to, and not entirely because of, the widespread decline in caribou. This is the hypothesis advanced by Andruko et al (2020), who posit that the expansion of deciduous shrub cover observed in plots on the summer and fall range of the Bathurst herd from 2006-2016 was too great to be explained by the climate warming measured during the same period.…”
Section: Vegetation Change and Caribou Population Dynamicsmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, increases in shrub cover have been shown to influence the composition of tundra vegetation (Fraser et al 2014, Myers-Smith et al 2019 and to alter biogeochemical feedbacks (Christiansen et al 2018, Wilcox et al 2019. Shrubification can also impede travel across tundra landscapes and can change the distribution and availability of culturally significant plants (e.g., berry plants; Cuerrier et al 2015;Anderson et al 2018; and wildlife (Andruko et al 2020). Investigations of the ecological processes that cause spatial variability in shrubification are important for predicting where future changes may occur in Arctic and Subarctic environments.…”
Section: Introductionmentioning
confidence: 99%